In situ temperature measurement on the metal/oxide/electrolyte interface during the anodizing of aluminum. Issue 1 (1st June 2011) - Schneider, M.; Lämmel, C.; Heubner, C.; Michaelis, A.
Abstract The temperature development during anodizing processes plays a key role in the case of industrial hard anodizing processes. Commonly, only the bath temperature is controlled; although it is well known that the bath temperature can significantly deviate from the temperature across the interface metal/oxide/electrolyte no investigation is known which shows the temperature deviation in this area. The authors have built a special experimental setup which allows a local temperature measurement across the interface. The results show the possibility of local resolved temperature measurements and the calculation of the heat flow into the metal and the anodizing bath. Based on this knowledge a target control of the current‐voltage‐regime avoids the formation of thermally caused cracks in hard anodized layers.